The Deep History of Ritual and Mythology: New Terrain in the Study of Religion. (March 2014) - Tsonis, Jack
<x xml:space="preserve">Abstract</x> Over the last two decades new forms of macrohistory have emerged that unite broad scientific timescales with the shorter timescales of human history. But although we have witnessed major strides in "big history" alongside a slew of works on the evolution of human culture, up to now there has been little sustained integration of the new paradigms with traditional fields of humanistic scholarship. This is particularly the case with "evolutionary" treatments of religion. However, a connection has finally been established, and the two provocative books reviewed in this article have opened up new terrain in the study of religion. The review is largely descriptive but closes by noting several reservations about both works.